Evolution of Conceptions of Science Policy, Technology and Innovation and institutional models in Uruguay (Management and Connections Journal, 2013)
DOI: http://dx.doi.org/10.13071/regec.2317-5087.2012.1.1.4025.8-43The institutional history of Uruguay in Science Policy, Technology and Innovation has more than half a century, during which, changed conceptions of science, policy models, institutions and organizations, in a parallel with the developments in Latin America and globally. To analyze this story, it is divided into several stages, with greater emphasis on the origins of the so-called linear model of innovation in the mid-twentieth century and its transfer to the countries of the region and deepen the analysis of the most recent institutional changes in the country and its relationship with the various disputed conceptual paradigms, in the context of systemic models.